CRITERIA FOR THE RETURN TO SPORT AFTER RECONSTRUCTION OF THE ANTERIOR CRUCIATE LIGAMENT (RACL) - Heba Alaeddine; Samar Delbani; Hassane Kheir Eddine; Khodor Haidar Hassan; Hassan Karaki (European Scientific Journal, ESJ, 2015)
Background: One of the objectives of the reconstruction of the anterior cruciate ligament (RACL) is the return of athletes to existing activity before the injury. Thus, it is essential to understand the variables that influence the return. Associations between the return to sport and the variables representing the strength of the quadriceps, instability and symmetry of the members, and the psychological state have not been studied in athletes following the RACL. Purpose: The purpose of this study is to summarize the literature relating to the proposed variables to be associated with the return to sport following a reconstruction of the anterior cruciate ligament. Method: During this study, we searched electronic databases, PubMed, Medline, Embase, and Cochrane Database to find the most recent articles about returning to the sport after the RACL criteria. Therefore, the articles included in this review meets these criteria: 1) patients who underwent a RACL; 2) reported at least one measurement of quadriceps strength, symmetry between members, and the psychological state; 3) the return to the sport identified by subjective measures or action to identify the level of sports participation of patients; and 4) any relationship analysis between the measures and the return to sport. Conclusion: Despite the fact that there are a number of important criteria influencing the return to sport, some have remained critical which have been considered and supported. By analyzing the items, the following results were obtained as described below: A quadriceps strength [IQ = 90%] and a motivating psychological state are the two criteria that ensures sport participation and reduction of the rate of re-injury or injury to the contralateral side. However, other criteria should not be neglected, with a view of their interaction with quadriceps strength and psychological status influence on the overall condition of the athlete wishing to return to the sport.